A time-optimal control problem for a set-valued linear control system - Komleva, T. O.; Plotnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.9We consider the time-optimal control problem for a set-valued linear control system in the case where a section of the solution of the system coincides with a target set.  For this problem, we obtain the solvability conditions as well as the optimal time and optimal controls.  The results are illustrated by model examples.